Methods for polymer-stabilization of molecular orientation in LC-waveguiding structures - Rutkowska, Katarzyna Agnieszka; Chychłowski, Miłosz (Photonics Letters of Poland, 2018)
In this letter we present a new way for constructing and developing LC-based waveguiding structures. Specifically, liquid crystalline material enriched with monomer in the proper proportions is implemented in our approach and a waveguide geometry can be created in the LC cell thanks to the photo-polymerization process allowing for LC molecules to be suspended in desired position and orientation. The latter can be enforced by external fields and UV-irradiation can be performed trough the mask of desired geometry. In this way, regions with different molecular textures (e.g. planar and homeotropic) and thus waveguiding structures can be easily created within LC layer. The main idea of this letter is not only to show a prove-of-concept of the polymer-imposed LC stabilization for such planar optical devices but to discuss differences in methodology of their practical realization. Full Text: PDF References Q. Li, Liquid crystals beyond displays: chemistry, physics, and applications (John Wiley & Sons, 2012). CrossRef J.P. Lagerwall, G. Scalia, Current App. Phys. 12, 1387 (2012). CrossRef A. Ciferri, Polymer liquid crystals (Elsevier, 2012). DirectLink D. Yang, Fundamentals of liquid crystal devices (John Wiley & Sons, 2014). CrossRef L. Vicari, Optical applications of liquid crystals (CRC press, 2016). DirectLink I. Dierking, Adv Mater 12, 167 (2000). CrossRef K. Rutkowska, M. Chychłowski, M. Kwaśny, I. Ostromęcka, J. Piłka, U. Laudyn, "Light propagation in periodic photonic structures formed by photo-orientation and photo-polymerization of nematic liquid crystals", Opto-Electr. Rev. 25, 118 (2017). CrossRef K A. Rutkowska, M. Chychłowski, U.A. Laudyn, Proc. SPIE 10325, 1032506 (2017). CrossRef B. Turowski, K.A. Rutkowska, Phot. Lett. Poland 9, 82 (2017). CrossRef H. Ren, Y. Lin, S. Wu, Opt. Commun. 261, 296 (2006). CrossRef V. Mucci and C. Vallo, J Appl Polym Sci 123, 418 (2012). CrossRef U.A. Laudyn, M. Kwaśny, K. Jaworowicz, K.A. Rutkowska, M.A. Karpierz, G. Assanto, Phot. Lett. Poland 1, 7 (2009). CrossRef M.S. Chychłowski, S. Ertman, E. Nowinowski-Kruszelnicki, T.R. Woliński, Mol. Cryst. Liquid Cryst. 553, 127 (2012). CrossRef